Talent acquisition and talent engagement practices significant impact over employee satisfaction - Marrybeth, Jackqueen Keith; Brackz, John Stave; Hadson, William Boy; Zlong, Marcus Sandy (International research journal of management, IT and social sciences, 2019)
It is observed that talent acquisition and talent engagement practices have a significant impact on employee satisfaction in the deemed universities. It is also disclosed that talent development and talent retention practices are found to be insignificant. It clearly indicates that the deemed universities are keen on talent acquisition and talent engagement, but they are failed in implementing talent development as well as talent retention strategies. Further, this analysis unveiled that talent acquisition and talent development practices have a significant impact on employee satisfaction in business schools. It is also disclosed that the talent engagement and talent retention practices are found to be insignificant. It clearly indicates that business schools are keen on talent acquisition and talent development, but they are failed in implementing talent engagement as well as talent retention strategies.